Extractable impurities from fluoropolymer-based membrane filters – interference in high-throughput, untargeted analysis - Perng Yang Puah; Dexter Jiunn Herng Lee; Ken Hing Mak; Hui Jun Ang; Hsing-Chang Chen; Pak Yan Moh; Siat Yee Fong; Yee Soon Ling (Royal Society of Chemistry, 2019)
The removal of particles using fluoropolymer-based membrane filters is usually done so to prolong the life span of an analytical column, prevent hardware damage, and reduce signal suppression. Ironically, these membrane filters tend to leach impurities into the samples as the samples are filtered through them. These impurities have the potential to affect the researcher's interpretation in high-throughput, nontargeted analysis. In this study, extractable impurities from different brands of fluoropolymer-based membrane filters present in the filtrate filtered using the said filters were investigated. The results demonstrated that different brand membrane filters and materials tend to elute vastly different numbers of impurities. There were instances whereby the extractable impurities persisted in both the membrane filter and the filtrate despite the filter being pre-conditioned (up to 3 times). Principle component analysis revealed that filtrates at different purge intervals are distant from the unfiltered samples. Preconditioning of the PTFE membrane filters could potentially reduce the number of extractable impurities across the tested brands. PVDF filtrates, however, tend to co-cluster with their respective brands, thus suggesting that dissimilarity persists in brands following conditioning. As such, pre-conditioning of the PTFE membrane filters should be encouraged so as to reduce false positive results, while the use of PVDF membrane filters for mass-spectrometry-based untargeted analysis is not advisable as extractable impurities would still persist after 3 rounds of conditioning. Neither the use of different filter brands, nor the use of different filter materials in a sample batch are encouraged as different membrane materials or brands could potentially elute varying impurities.